PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KEADILAN DISTRIBUTIF DAN PROSEDURAL KOMPENSASI TERHADAP KEPUASAN KERJA PERAWAT DI RSU PKU MUHAMMADIYAH BANTUL - Meise Satriani; Heru Kurnianto Tjahjono; Qurratul 'Aini (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2012)
Background: RSU PKU Muhammadiyah Bantul is a privately-owned public hospital that has been burgeoning. Leadership held at PKU Muhammadiyah Hospital in Bantul today is a transformational leadership. While, for motivating employee, the management of the hospital strives to provide adequate and fair compensation based on employee status, class rank and tenure. Hence, the compensation system will encourage every employee to give excellent service for each patient. Methodology: The research is a quantitative analysis using cross-sectional survey method. Data is obtained by disseminating questionnaire to the population, the whole permanent employee up to 104 respondents. Result: The statistical result indicates that management’s policy transformational leadership and distributive justice and procedural compensation rate affect to the satisfaction of work of the nurses at RSU PKU Muhammadiyah Bantul. Summary: Regarding to the result of the research, management’s policy to appreciate its employee through a good and fair compensation can significantly improve the satisfaction of work of the nurses at RSU PKU Muhammadiyah Bantul. Moreover, the management should maintain a workable situation and pay a lot of attention to the nurses.